Late traumatic diaphragmatic rupture complicated by haemothorax and strangulation of the stomach: A case report. Issue 6 (June 2020) - Xiao, Jian-Chun; Ma, Li-Yuan; Li, Bing-Lu
Traumatic diaphragmatic rupture (TDR) is an uncommon but life-threatening condition often caused by blunt or penetrating trauma. Symptoms may appear late resulting in delayed or missed diagnosis. We report here a case of a 28-year-old man who presented with left subcostal pain and vomiting after recently binge drinking alcohol. He had experienced bilateral rib fractures two years previously. Computed tomography (CT) showed massive left pleural effusion and pleural fluid drained by thoracentesis had a bloody appearance. The patient developed septic shock but emergency surgery showed no active bleeding. Enhanced-CT showed herniated stomach with ischemic necrosis in the left thoracic cavity. Total gastrectomy and diaphragmatic repair were successful and the patient had an uneventful recovery. A high index of suspicion is necessary when evaluating haemothorax, especially in patients with recent or previous thoraco-abdominal injury.